2007
DOI: 10.1172/jci31242
|View full text |Cite
|
Sign up to set email alerts
|

Local production of angiotensin II in the subfornical organ causes elevated drinking

Abstract: . We generated double-transgenic mice expressing human renin (hREN) from a neuron-specific promoter and human AGT (hAGT) from its own promoter (SRA mice) to emulate this expression. SRA mice exhibited an increase in water and salt intake and urinary volume, which were significantly reduced after chronic intracerebroventricular delivery of losartan. Ang II-like immunoreactivity was markedly increased in the subfornical organ (SFO). To further evaluate the physiological importance of de novo Ang II production sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
139
2
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(158 citation statements)
references
References 50 publications
10
139
2
5
Order By: Relevance
“…Total RNA was isolated with TRIzol reagent (Invitrogen) according to the manufacturer's protocol. Reverse transcription (RT) was performed using 1 g of total RNA, containing (dT) [12][13][14][15][16][17][18] primers for quantitative real time PCR and SuperScriptII transcriptase (Invitrogen). Complementary DNA was amplified in reaction mixture containing 2.5 mM deoxynucleotide triphosphate mix, 10 mM specific primers, and rTaq DNA polymerase (Takara, Ohotsu, Japan) under the following conditions: 95°C for 30 s, 55 or 60°C for 30 s, and 72°C for 30 s for 40 cycles in a GeneAmp PCR system 9700 (Applied Biosystems, Foster City, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was isolated with TRIzol reagent (Invitrogen) according to the manufacturer's protocol. Reverse transcription (RT) was performed using 1 g of total RNA, containing (dT) [12][13][14][15][16][17][18] primers for quantitative real time PCR and SuperScriptII transcriptase (Invitrogen). Complementary DNA was amplified in reaction mixture containing 2.5 mM deoxynucleotide triphosphate mix, 10 mM specific primers, and rTaq DNA polymerase (Takara, Ohotsu, Japan) under the following conditions: 95°C for 30 s, 55 or 60°C for 30 s, and 72°C for 30 s for 40 cycles in a GeneAmp PCR system 9700 (Applied Biosystems, Foster City, CA).…”
Section: Methodsmentioning
confidence: 99%
“…This suggests a possible link between vascular and skeletal systems. Renin angiotensin system (RAS) is operating not only systemically but also locally in several tissues, and bone microenvironments have been studied in this regard (15,16). Osteoblasts and osteoclasts express angiotensin II type 1 receptor in cell cultures (17)(18)(19), suggesting the existence of local RAS in bone.…”
mentioning
confidence: 99%
“…It is thought that the active peptides angiotensin II, III, or IV may have roles within the brain in functions as diverse as the regulation of cardiovascular and fluid homeostasis (2,3,11,19,35,40,41,46), reproduction (15), thermoregulation (28), memory (49), cognition, emotional responses to stress and anxiety, cerebral blood flow regulation, and brain developmental processes (39). However, some studies have questioned whether angiotensin is a neuropeptide because of its very low abundance in brain (23) and have proposed that an alternative endogenous ligand may act on angiotensin receptors in the brain (6).…”
mentioning
confidence: 99%
“…Recently, Sakai et al [5] generated doubletransgenic mice expressing human renin (hREN) from a neuron-specific promoter and human AGT (hAGT) from its own promoter (SRA mice) to emulate this expression [4]. SRA mice exhibited an increase in water and salt intake and urinary volume, which were significantly reduced after chronic intracerebroventricular delivery of losartan.…”
mentioning
confidence: 99%
“…Whether or not Ang II is the final mediator of any central nervous system responses is also unclear. Strong argument has been made for a central aminopeptidase that degrades Ang II to the heptapeptide Ang [2][3][4][5][6][7][8], which is also known as Ang III. FournieZaluski et al [13] reported that brain Ang III exerts a tonic stimulatory effect on blood pressure in the desoxycorticosterone (DOCA)-salt rat that is characterized by a depressed systemic but a hyperactive brain reninangiotensin system.…”
mentioning
confidence: 99%